2008
DOI: 10.1002/ajmg.a.32513
|View full text |Cite
|
Sign up to set email alerts
|

Using second trimester ultrasound and maternal serum biomarker data to help detect congenital heart defects in pregnancies with positive triple‐marker screening results

Abstract: Congenital heart defects (CHDs) are the most common of all birth defects. For many newborns with a CHD, prenatal versus postnatal detection is associated with substantially decreased morbidity and mortality risks. Although technological advances in fetal echocardiography have led to an increased capacity to detect CHDs prenatally, pregnancies without an identified risk factor are not routinely screened. With the aim of identifying pregnancies at increased risk for CHDs, this study examined the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…All sources are mandated by California law to report diagnosed chromosomal abnormalities (whether diagnosed by karyotype or microarray) to the program. [20][21][22][23][24] Information on CCHDs was collected by the linkage of screening records with all hospital discharge records through 1 year of age for each study infant (wherein records were linked with the use of multiple identifiers [baby and mother date of birth; baby first and last name; mother first, last, and maiden name, address, phone number, and hospital of baby birth]). These records include all inpatient discharge information that is submitted to the state each time a patient is treated in a licensed general acute care hospital in California and includes all diagnoses present at the time of discharge based on 4-or 5-digit codes from the Ninth Revision of the International Classification of Diseases.…”
Section: Methodsmentioning
confidence: 99%
“…All sources are mandated by California law to report diagnosed chromosomal abnormalities (whether diagnosed by karyotype or microarray) to the program. [20][21][22][23][24] Information on CCHDs was collected by the linkage of screening records with all hospital discharge records through 1 year of age for each study infant (wherein records were linked with the use of multiple identifiers [baby and mother date of birth; baby first and last name; mother first, last, and maiden name, address, phone number, and hospital of baby birth]). These records include all inpatient discharge information that is submitted to the state each time a patient is treated in a licensed general acute care hospital in California and includes all diagnoses present at the time of discharge based on 4-or 5-digit codes from the Ninth Revision of the International Classification of Diseases.…”
Section: Methodsmentioning
confidence: 99%
“…These 68 obese women were selected from a larger cohort of 1000 women, who all had first and second trimester prenatal screening for aneuoploidies and neural tube defects through the California Genetic Disease Screening Program from July 2009 through December 2010. Details of the larger cohort have been described previously [18–25]. …”
Section: Methodsmentioning
confidence: 99%
“…Details about the California Expanded AFP Screening Program including information about how serum is tested, how multiple of the median (MoM) values are calculated, and about how chromosomal defects and NTD diagnoses are tracked by the state have been reported elsewhere (Craig et al , 2007; Jelliffe‐Pawlowski et al , 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Recent work by our group examining the association between typically collected second trimester serum biomarkers [alpha‐fetoprotein (AFP), human chorionic gonadotrophin (hCG), unconjugated estriol (uE3)] and CHDs among pregnancies with screen positive results for Down syndrome, trisomy‐18 (T‐18), neural tube defect (NTD), or Smith–Lemli–Opitz syndrome (SLOS) suggested that serum biomarker patterns could potentially be used when evaluating CHD risk (Jelliffe‐Pawlowski et al , 2008, 2009). Using independent samples, both studies found that abnormally high or low hCG levels were strongly associated with an increased risk for CHDs in screen positive pregnancies.…”
Section: Introductionmentioning
confidence: 99%